Assemblies of single-walled carbon nanotubes generated by covalent cross-linking with organic linkers1. Issue 13 (7th April 2015) - Kumar, Ram; Rao, C. N. R.
<x xml:space="preserve">Abstract</x> Assemblies of covalently linked single-walled carbon nanotubes with superior gas adsorption properties have been prepared and characterized.